A Comprehensive Analysis of Production Efficiency: A Tax Reform Perspective - Laurence Jacquet; Etienne Lehmann (CESifo GmbH, 2024)
Policies that impact the production sector, such as intermediate goods taxation (e.g. taxing robots) and trade liberalization create winners and losers. When do we need to integrate pre-distribution concerns in the design of these production policies? Should we consider the endogenous changes of factor prices in tax formulas? We show that the answers to these two questions depend only on the features of the income tax system. More precisely, can the tax system distinguish incomes from each factor of production? Can it be reformed along the so-called "GE-replicating directions", reproducing the impact of factor price adjustments on taxpayers' utility? If the answer to either question, or both, is "no", the design of production policies should also take into account its pre-distributive role and all formulas reveal novel, empirically implementable "GE multipliers". These multipliers shape tax systems to correct for market failures as well as for the effects of price adjustments. In contrast, if the answer to both questions is "yes", it is Pareto-improving to design production policies solely to enlarge production possibilities and the "GE multipliers" shape the income tax system only to account for market failures. We illustrate these insights with realistic tax systems and practical examples of production policies.
Keywords: H21; H22; H23; H24; L50; F13; 330; production efficiency; nonlinear income taxation; several income sources; endogenous prices